Effect of weather on stock market: A literature review and research agenda - Chinnadurai Kathiravan; Murugesan Selvam; Balasundram Maniam; Munusamy Dharani (Cogent Economics & Finance, 2021)
The paper presents a systematic review of the research work, published on the topic of weather effects and stock market behavior. The objectives of the study were to examine the current status of research, by collecting the literature, in the area of weather effects and stock market behavior. In the process, the study would reveal the current status to the budding researchers. In this study, the authors critically assessed and examined fifty one research studies, published from 1993 and 2019, in different regions across the globe. A systematic literature review for this study has been made using Google Scholar. The present study found that number of research works on the weather effects and stock market behavior had increased marginally during the recent time period, especially from the beginning of Twenty First Century. Among the different weather factors, temperature was wildly used for research. Finally, this paper reveals some significant research gap to advance the research agenda for future research.
Keywords: G02; G11; G12; 330; Literature Review; Research Methodology; Systematic Review